Effects of physical therapy on improving disc height index, postural stability, pain and function in persons with discogenic low back pain - Muhammad Osama; Aamer Naeem; Sameen Tariq; Sumera Mushtaq; Furqan Ahmed Siddiqi; Sabah Afridi (Journal of the Pakistan Medical Association)
Objective: To determine if physical therapy is capable of improving disc height index, pain, functional disability, lumbar range of motion, postural stability and gait in persons with discogenic low back pain.